#TITLE_ALTERNATIVE# - ALGIFARI FIRDAUSYA (NIM : 12212087), MOCHAMAD
Gas reservoir with water drive mechanism has a large aquifer in the bottom of the reservoir. Gas recovery from this type of reservoir can be lower than expected because water influx increase water saturation in the reservoir, make the gas trapped and can not be produced. Water production on gas wells will reduce the gas flow rate and can shut off the well in a fast time. In addition, gas wells in the reservoir of this type is susceptible to accumulation of fluid in the bottom of the well (liquid loading). Liquid loading is an accumulation of fluid in the wellbore due to reduced reservoir pressure due to reservoir depletion mechanism. This often occurs in wet gas reservoirs but can also occur in dry gas reservoirs when the invasion of water into the well bore from a nearby aquifer. In this thesis, we learn about production optimization strategy in addressing the problems of production through optimal determination of perforation intervals. The strategy used was to design the optimum perforation interval fractions used from the beginning to the end of production and the closure of the perforation interval when the rate of water production increased. The strategy generates the largest gas recovery factor achieved in the design of the initial perforation interval fraction of 60% were used until the end of production and optimum perforation interval closure strategy is not effective in the production of the reservoir. In gas wells, perforation interval closure will reduce gas recovery factor even while reducing the amount of produced water. By selecting the optimum perforation interval, the gas can be obtained optimally by minimizing the amount of produced water.